Scaffolding untuk Pembelajaran Matematika di Kelas Inklusi - Ukhti Raudhatul Jannah; Hairus Saleh; Anik Wahidah (JKPM (Jurnal Kajian Pendidikan Matematika), 2019)
This study aims to describe the process of scaffolding in mathematics learning in inclusion classes. This research uses qualitative descriptive method and data collection technique is done by observation, interview and documentation. Then the data that have been collected is analyzed by the reduction stage, presentation and conclusion. Based on the result of the research, it can be concluded that Scaffolding used in this research refers to Anghilery scaffolding which consists of 3 levels, namely (1) Environmental Provisions, level (2) Explaining, Reviewing and Restructuring and Leveling (3) Developing Conceptual Thinking. Scaffolding given to students with Special Needs during the learning process in the inclusion class depends on the level of mistakes made by students with Special Needs.The error is seen from the results of working instrument before being given scaffolding. Then from the mistakes,  the teacher provides scaffolding to students with special needs according to their needs to correct their mistakes.